Alterations in the trapezius muscle in young patients with migraine – A pilot case series with MRI. (May 2015) - Landgraf, M.N.; Ertl-Wagner, B.; Koerte, I.K.; Thienel, J.; Langhagen, T.; Straube, A.; von Kries, R.; Reilich, P.; Pomschar, A.; Heinen, F.
Abstract Background/purpose Migraine is frequent in young adults and adolescents and often associated with neck muscle tension and pain. Common pathophysiological pathways, such as reciprocal cervico-trigeminal activation, are assumed. Tense areas within the neck muscles can be clinically observed many patients with migraine. The aim of this pilot case study was to visualize these tense areas via magnet resonance imaging (MRI). Methods Three young patients with migraine were examined by an experienced investigator. In all three patients tense areas in the trapezius muscles were palpated. These areas were marked by nitroglycerin capsules on the adjacent skin surface. Results The MRI showed focal signal alterations at the marked locations within the trapezius muscles. Conclusion Visualization of palpable tense areas by MRI may be usefully applied in the future to help elucidate the underlying pathophysiological processes of migraine.